Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

Please help me with this problem

Please Help Me With This Problem class=

Sagot :

Answer:

-36

Step-by-step explanation:

6^2+(y-x)

=>                 6^2+[-77 - (-5)]

=>                 6^2+[-77+5]

=>                 6^2+(-72)

=>                 36+(-72)                            [6^2 = 36]

=>                 -36

 

can you mark me brainliest?

Hello-

6² + (y - x) is our equation. And wonder of wonders, our x and y values are given! What a beautiful thing, having both given to us.

x = -5

y = -77

Let's plug our given values into our equation for x and y. Like so-

6² + (y - x) becomes 6² + (-77 - (-5))

In math, we must do whatever operations are contained within parentheses first and foremost. So we must subtract -5 from -77. That, by the way, equals -72.

6² + -72

Now we do our exponents, or powers.

6² = 36

36 + -72

Now we do the easiest part - adding.

32 + -72 = -36

So the answer to this problem (if I've done my algebra correctly) is -36.

Hope this helps.